An equilibrium analysis of the rise in house prices and mortgage debt - Shaofeng Xu (Bank of Canada, 2013)
This paper examines the contributions of population aging, mortgage innovation and historically low interest rates to the sharp rise in U.S. house prices and mortgage debt between 1994 and 2005. I construct an overlapping generations general equilibrium housing model and find that these three factors together account for over half of the increase in house prices and most of the increase in mortgage debt during this period. Population aging contributes to rising house prices and mortgage debt, but it accounts for only a small portion of their observed changes. Meanwhile, mortgage innovation significantly increases the mortgage borrowing of various age cohorts, but it has a trivial effect on house prices because interest rates rise due to higher demand for mortgage loans. This increases households' savings in financial assets and leaves their housing assets nearly unchanged. The observed run-up in house prices can, however, be justified in an open-economy setting where interest rates fall due to a global saving glut. Declining interest rates force households at prime saving ages to reallocate their wealth from financial assets to housing assets, which dramatically drives up house prices.
Keywords: E21; E44; G11; R21; 330; Asset pricing; Credit and credit aggregates; Economic models